Penerapan Criminal Justice System Yang Humanis Dan Eefektif Sebagai Paradigma Baru Pembaharuan Sistem Peradilan Pidana Di Indonesia - Rahayu, Setyaning; Sidik Sunaryo (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Indonesia's criminal justice system is currently facing serious challenges. Problems such as prison overcapacity, injustice in law enforcement, and inadequate protection of human rights are major issues. In this study, the researcher applied a systematic review method and meta-analysis of various literatures and recent studies to examine the implementation of a new paradigm in a more humane and effective criminal justice system in Indonesia. The findings show that reforms in the criminal justice system need to emphasize the principles of restorative justice, protection of human rights, as well as collaboration between law enforcement agencies. Collaboration is needed to demonstrate shared commitment, update regulations, and increase the capacity of law enforcement agencies in order for Indonesia's criminal justice system to achieve real justice and protect human rights.